Regulate or Prohibit: a Review of Hidden Prostitution Law Enforcement Policies in Indonesia - Mahardika, Eriana; Garduño, Lizette Ramos; Dar Nasser, Montaser Faris (UIN Sunan Kalijaga Yogyakarta, 2023)
Prostitution is an act that is contrary to the norms that exist in society because this act can cause unrest in the community and disrupt the order of life in the surrounding community. Prostitution deviates from the norms of decency where a woman or a man sells himself to get satisfaction from lust. Prostitution is spreading rapidly in Indonesia. Many prostitutions are committed under the guise of, among others, Reflexy Massage Parlors, Beauty Salons, and SPA. This study is motivated by the problem of the practice of hidden prostitution under the guise of these business premises in Indonesia, especially the Sleman Regency area, which are almost entirely unexposed and untouched by law enforcement officials but have the potential for negative impacts on society both socially, psychologically, religiously and culturally. This article aims to find out how law enforcement is against the hidden practice of prostitution under the guise of massage parlors, salons, and spas in Indonesia, especially in the district of Sleman. This study combined field and library research, using an empirical juridical approach with a descriptive-analytic method to explain the data. It also used legal system theory to analyze. This study showed no clear and specific regulations that regulate or prohibit prostitution firmly. So far, the Police and Civil Service Police Unit (Satpol PP) have enforced the law based on Regional Regulation No. 15 2012 concerning Tourism Business Registration in Sleman. However, the participation of every stakeholder in society with local wisdom that has existed so far is expected to create legal awareness about hidden prostitution.